The role of Islamic work ethic in moderating the influence of human relations, work environment, and work discipline on employee performance - Astana Intanulqoir Astana; Endah Nur Fitriyani Endah (Journal of Islamic Economics Management and Business (JIEMB), 2025)
Employee performance plays a pivotal role in determining organizational success, particularly in companies that rely heavily on human capital. This study examines the influence of human relations, work environment, and work discipline on employee performance and investigates the moderating role of Islamic work ethic in these relationships. Drawing upon Human Capital Theory, the research adopts a quantitative approach involving 100 employees of PT. PMJ in Central Java, selected using the Slovin formula. Data were collected through structured questionnaires and analyzed using statistical inference and Moderated Regression Analysis (MRA). The findings reveal that human relations and work environment have a significant positive impact on employee performance, while work discipline shows a positive but insignificant effect. Furthermore, the Islamic work ethic significantly moderates the relationship between the work environment and employee performance, indicating that employees who embody Islamic values respond more positively to supportive working conditions. However, the moderating effect of Islamic work ethic is not evident in the relationships between human relations or work discipline and performance. These results underscore the importance of cultivating an Islamic ethical framework that aligns with human capital development and workplace well-being. The study contributes to the growing literature on Islamic management by emphasizing the role of ethical and spiritual values in enhancing employee performance. Practically, it suggests that organizations should integrate Islamic work ethics—such as honesty, diligence, and sincerity—into management practices to strengthen employee motivation, productivity, and organizational effectiveness.